Pengaruh Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Terhadap Perkembangan Karakter Moral Peserta Didik Di Kelas XI Akuntansi Dan Keuangan Lembaga (AKL) SMK Ciledug Al-Musaddadiyah Garut - Abdillah, Syaik; Andini Nurjanah, Ismi (STAI Al-Musaddadiyah Garut, 2023)
Islamic Religious Education and Moral Education are integral parts of the educational system in Indonesia. These subjects are essential for imparting knowledge, shaping attitudes, personality, and skills of students in practicing Islamic teachings, and are taught at all educational levels. This study addresses the following research questions: (1) How is Islamic Religious Education and Moral Education taught in the 11th grade of the Accounting and Finance (AKL) program at SMK Ciledug Al-Musaddadiyah Garut? (2) What is the moral character of students in the Islamic Religious Education and Moral Education classes in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut? (3) What is the impact of Islamic Religious Education and Moral Education on the moral character development of students in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut? Based on these questions, the objectives of this research are: (1) To understand how Islamic Religious Education and Moral Education are conducted in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut. (2) To analyze the moral character of students in the Islamic Religious Education and Moral Education classes in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut. (3) To determine the impact of Islamic Religious Education and Moral Education on the moral character development of students in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut. This research employs an inferential quantitative method, collecting data or information about the phenomena being studied. Data collection techniques include questionnaires distributed to 25 respondents, observations, and documentation studies. Data analysis is conducted using statistical data analysis methods. The findings of this research conclude that there is a significant impact of Islamic Religious Education and Moral Education on the moral character development of students in the 11th grade of the AKL program at SMK Ciledug Al-Musaddadiyah Garut. Keywords: Islamic Religious Education and Moral Education, Moral Character Development of Students